EFFECTS OF PERSULFATE, PEROXIDE ACTIVATED PERSULFATE AND PERMANGANATE OXIDATION ON TREATABILITY AND BIODEGRADABILITY OF LEACHATE NANOFILTRATION CONCENTRATE - Guvenc, Senem Yazici; Varank, Gamze; Demir, Aumet (TECHNICAL UNIV WROCLAW, 2020)
The effects of persulfate (PS), peroxide activated persulfate (P-PS) and permanganate (PM) oxidation processes on leachate nanofiltration (NF) concentrate treatment have been activated. Additionally, COD fractions were determined and compared before and after each oxidation process. The total COD removal efficiencies by the oxidation processes using PS, P-PS, and PM as the oxidants were determined to be 24.5%, 32.9%, and 39.5%, respectively. The biodegradable COD fraction increased from 6.37% to 9.25%, 11.51%, and 13.64% after the PS, P-PS, and PM oxidation processes, respectively. About 25%, 34%, and 46% removal efficiencies of the inert COD content of the concentrate were obtained after the PS, P-PS and PM oxidation processes, and the soluble COD fraction increased from 71.1% to 87.2%, 89.0% and 84.6% by the PS, P-PS and PM oxidation processes, respectively. Although the highest removal efficiencies were achieved by PM oxidation with the lowest operational cost, all of the processes may be suggested as efficient methods for conversion of insoluble COD into the soluble COD fraction and for inert COD removal. The results of the study showed that the PS, P-PS, and PM oxidation processes may be effectively utilized as post-treatment techniques for leachate NF concentrate treatment.
Keywords: UV-LIGHT; WATER; OZONE; Engineering